USING THE FIVE LANGUAGES OF LOVE IN TEACHING - Mahmud, Salami; Wanty Khaira; Nida Jarmita (JKA, 2024)
This article aims to explain the importance of applying the five love languages ​​in teaching and how it can have a positive impact on various aspects of the teaching and learning process. The five love languages ​​is a concept developed by Dr. Gary Chapman, adapted in an educational context to strengthen relationships between teachers and students and create a positive and supportive learning environment. This adaptation involves five main approaches, namely supporting words, quality time, gift giving, acts of service, and physical touch. Applying the five love languages ​​in teaching not only helps create a more enjoyable and productive learning environment, but also contributes to students' emotional and social development. By adapting this approach to each student's individual needs, teachers can increase student motivation, self-confidence, and academic performance, as well as build stronger, supportive relationships